Correlation between Doppler and fhlebography in the diagnosis of clinically suspected acute deep venous thrombosis. - Sciuto, Fernando; Mazza, Milton; Rudnitzky, Omar; Blanco, Raúl; Blanco, Adriana; Sueta, Patricia; Portos, Ruben; Corradi, Daniel (Cirugía del Uruguay, 1987)
Symptomatic patients with suspicion of deep venous thrombosis create management problems due to the imprecision of the clinical diagnosis, A prospective study was designed in order to determine the utility of Doppler in this situation, using phlebography as diagnosis standard. An ov1:1rall sensibility of 94% and a specificity of 90% was found.